Quantification of entry phenotypes of macrophage-tropic HIV-1 across a wide range of CD4 densities - Joseph, Sarah B; Arrildt, Kathryn T; Swanstrom, Adrienne E; Schnell, Gretja; Lee, Benhur; Hoxie, James A; Swanstrom, Ronald (Journal of virology, 2014)
Defining a macrophage-tropic phenotype for HIV-1 to assess a role in pathogenesis is complicated by the fact that HIV-1 isolates vary continuously in their ability to enter monocyte-derived macrophages (MDMs) in vitro, and MDMs vary in their ability to support HIV-1 entry. To overcome these limitations, we identified consistent differences in entry phenotypes between five paired blood-derived, T cell-tropic HIV-1 env genes, four of which are CCR5-using (R5) and one of which is CXCR4-using (X4), and cerebrospinal fluid (CSF)-derived, R5 macrophage-tropic env genes. We performed entry assays using the CD4- and CCR5-inducible Affinofile cell line, expressing a range of CD4 levels that approximates the range from MDMs to CD4(+) T cells. The macrophage-tropic viruses were significantly better at infecting cells expressing low levels of CD4 than the T cell-tropic viruses from the same subjects, with the titration of CD4 providing a distinctive and quantitative phenotype. This difference in CD4 utilization was not due to macrophage-tropic viruses being CD4 independent. Furthermore, macrophage-tropic viruses did not differ from paired T cell-tropic viruses in their ability to use low levels of CCR5 (tpaired = -1.39; P = 0.24) or their use of an alternative conformation of CCR5. We also infected MDMs with a panel of viruses and observed that infectivity of each virus differed across four donors and between three preparations from a single donor. We concluded that the evolutionary transition from replication in T cells to that in macrophages involves a phenotypic transition to acquire the ability to infect cells expressing low levels of CD4 and that this phenotype is more reliably measured in Affinofile cells than in macrophages. IMPORTANCE HIV-1 typically infects memory T cells by using CD4 and CCR5 to enter cells. The virus evolves to infect new cell types by changing the coreceptor from CCR5 to CXCR4 to infect naive T cells or adapting to the use of low levels of CD4 to infect macrophages. However, defining the phenotype of macrophage tropism has been difficult due to inherent variability in the use of macrophages generated in culture to support entry of HIV-1. We describe the use of Affinofile cells with inducible and variable levels of CD4 to identify a signature phenotype for macrophage-tropic HIV-1. The ability to define HIV-1 variants that have evolved an entry phenotype that allows more efficient entry into cells with low levels of CD4 sets the stage for a clearer placement of these variants in HIV-associated pathogenesis.